Functional Polyurethane Coatings for Protection of Different Surfaces from Aggressive Environmental Factors - Savelyev, U.V.; Markovska, L.A.; Robota, L.P.; Parkhomenko, N.I.; Savelyeva, O.O. (Science and Innovation, 2024)
New polyurethane composites (PCs) have been created. They are multifunctional protective materials used as coatings, binders or impregnating materials. The PCs have high adhesion values. The PC-based materials are waterproof and resistant to aggressive biotic (abiotic) and anthropogenic factors (bio-corrosion, UV radiation, chemical agents). Being imbedded in polymer macro-chain the active compounds prolong the action of protective mechanisms of proposed materials thereby giving them an advantage over the existing substances.